Evaluation of bait use for mammal richness - Ribeiro, Renan L. A. [UNESP]; Bianchi, Rita C. [UNESP] (Walter De Gruyter Gmbh, 2020)
In this study, we aimed to evaluate the effectiveness of baits as a tool for estimating species richness for medium and large mammals. To this end, we installed 15 cameras in the Ecological Station of Jatai, Sao Paulo, Brazil (21 degrees 30'S - 47 degrees 40'W and 21 degrees 40'S/47 degrees 50'W). The cameras were placed in a grid with a distance of 1 km between each station. We randomly placed cameras with baits and those without baits and made observations for 4 weeks. Then, after a week's break, the treatments were inverted and continued for another 4 weeks. We estimated species richness based on the presence or absence of species using the Jackknife1 estimator in the EstimateS program and compared the treatments using the paired Wilcoxon test. Species composition and estimated richness did not differ between treatments with baits (S-Jack1 = 20.97 +/- 1.96) and those without baits (S-Jack1 = 20.95 +/- 1.95; W = 30 p = 0.15). The rarefaction curves between the treatments were similar, suggesting that the use of baits did not increase or reduce the number of species recorded. In addition, the use of baits did not significantly increase capture rates. Analysis of the costs of the different treatments showed that the use of baits increased the project costs by more than 4 times. The findings of this study suggest that, for species surveys, camera traps do not need to be baited.
Keywords: baits; community; composition; mammal survey; richness